Writing analytically - Rosenwasser, David (Harcourt Brace College, 1997)
The book offers a book-length treatment of analysis, a form of thinking and writing required in most college courses. It combines the two approaches (the process approach to writing and the critical thinking movement) to offer a guided tour of the thought processes inherent in anlytical thinking. It treats thinking skills not in isolated exercises but in the context of the writing process, offering step-by-step acocounts of how analyses are produced